b+166=-3b-6

Simple and best practice solution for b+166=-3b-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b+166=-3b-6 equation:


Simplifying
b + 166 = -3b + -6

Reorder the terms:
166 + b = -3b + -6

Reorder the terms:
166 + b = -6 + -3b

Solving
166 + b = -6 + -3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3b' to each side of the equation.
166 + b + 3b = -6 + -3b + 3b

Combine like terms: b + 3b = 4b
166 + 4b = -6 + -3b + 3b

Combine like terms: -3b + 3b = 0
166 + 4b = -6 + 0
166 + 4b = -6

Add '-166' to each side of the equation.
166 + -166 + 4b = -6 + -166

Combine like terms: 166 + -166 = 0
0 + 4b = -6 + -166
4b = -6 + -166

Combine like terms: -6 + -166 = -172
4b = -172

Divide each side by '4'.
b = -43

Simplifying
b = -43

See similar equations:

| 2b+6.3=13.2-28 | | -9x-5=x+385 | | x^2+10x+25+y^2-18y+81=64 | | a-324=-6a-9 | | a^3=512 | | -9z+4=z+234 | | 10x-11-rx=43 | | u+133=-9u+3 | | y/6-1/3=2 | | b+59=-b-5 | | 1/2m-3=2 | | b+59=b-5 | | z-58=-z-8 | | 2x+8=4x+22 | | -a+8=a+98 | | B-56=234 | | -a-9=a+47 | | 4a+5=2a+17 | | (a+4b)+(c-2d)=0 | | 12=22-2x | | 8=3k-3 | | 25+N-100=75 | | 11/20x-1/4x | | 10 x 1/L x 57.8 | | 15.5y+12=12 | | 9x+26=3x+20 | | 4x-3x^3=0 | | 3y+y=72 | | 5x-3x=3+4x | | y=8-x^2-2x | | 8/3:x=4/5:3 | | x+75=2x-20 |

Equations solver categories